Pengaruh Stres Kerja, Konflik Kerja dan Beban Kerja terhadap Kinerja Karyawan - Wahyu Muji Lestari; Lie Liana; Ajeng Aquinia (Jurnal Bisnis dan Ekonomi, 2020)
This study aims to analyze the effect of job stress, work conflict and workload on employee performance. This research used census research method. The population in this study were employees of PERUMDA Air Minum Tirta Jungporo Jepara, with a total of 120 people. The technique used in retrieving data in this study uses a survey method with questionnaire aids that contains four variables namely job stress (X1), work conflict (X2), workload (X3) and employee performance (Y). The test used was the instrument test, model test and multiple regression analysis test using SPSS 22. The results showed that job stress positively and significantly improved employee performance, work conflict did not improve employees, and workload significantly increased employee performance.